PENGARUH KOMBINASI TERAPI WALKING EXERCISE DAN TERAPI MUSIK KLASIK TERHADAP FATIGUE PADA PASIEN KANKER PAYUDARA: The Effect of Combination of Walking Exercise Therapy and Classical Music Therapy on Fatigue in Breast Cancer Patients - Anna Rufaida; Esti Yunitasari; Ilya Krisnana (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2020)
Background: Fatigue is a subjective feeling of physical, cognitive, emotional fatigue related to cancer or cancer treatment and fatigue that is felt to be not comparable to the activities carried out. Side effects that occur can interfere with before weighting, during or after treatment. Walking exercise, has been recognized as one of the most effective interventions to reduce cancer-related fatigue, so this non-pharmacological treatment can be an alternative option that can be done. Music therapy can also have a positive effect on patients with breast cancer. The purpose of this study was to analyze the effect of a combination of walking exercise and classical music therapy on fatigue in breast cancer patients. Method: this study is a quasi experimental study. The study sample was breast cancer patients who visited Surabaya health centers who met the criteria of inclusion and exclusion by simple random sampling (n = 48). The independent variable in this study was a combination of walking exercise and listening to classical music. The dependent variable is fatigue. Giving intervention combination of walking exercise and listening to classical music through module media and mp3. Measurement of fatigue using BFI (Brief Fatigue Inventory). The intervention was given for 3 weeks and carried out 3 measurements (pre test and post test). Test of statistical analysis using Wilcoxone signed rank test Results: In the treatment group there were differences in the value of fatigue before and after 4 weeks of interventions with combination walking and classical music. There were differences in fatigue before and after 4 weeks of walking exercise and classical music with sig values ??<0.05. In the control group the results of the Wilcoxone signed rank test showed no significant differences in fatigue before and after the 4th week of evaluation with a value of 0.04. Conclusion: Combination of walking exercise and listening to classical music can reduce fatigue in breast cancer patients. Keywords: walking exercise, music, fatigue, exercise, classical music, Mozart